Analisis Pengendalian Internal dalam Sistem Informasi Akuntansi Terhadap Penerimaan dan Pengeluaran Kas Studi Kasus PT. Pelabuhan Indonesia Cabang Belawan - Indah Wahyuni; Yenni Samri Juliati Nasution; Laylan Syafina (Universitas Katolik Widya Karya Malang, 2023)
This study aims to analyze the Internal Control System and to analyze the role of the Accounting Information System for cash receipts and expenditures at PT Pelabuhan Indonesia Belawan Branch. This research approach is descriptive by using qualitative data types. The research data conducted is in the form of primary data and secondary data. Where primary data is carried out by interviews, and secondary data in the form of evidence, records or historical reports that have been compiled in published and unpublished archives. The results showed the internal control system of the accounting information system of cash receipts and expenditures at PT. Pelabuhan Indonesia Belawan Branch is still not optimally implemented so it is not in accordance with the purpose of internal control. This is proven by the existence of control elements that have not been implemented, namely from elements of control activities and elements of risk assessment and accounting information systems at PT. Pelabuhan Indonesia has played a good role so that it can improve the internal cash control system.